Infections in hospitalised patients affected by end-stage diseases: a narrative overview. (2nd April 2022) - Sganga, Federica; Salerno, Andrea; Borghetti, Alberto; Fantoni, Massimo; Turriziani, Adriana; Barillaro, Christian; Bernabei, Roberto
Abstract : Aim: To analyse the presence and treatment of infections in hospitalised terminal patients by identifying potential risk factors. Methods: We conducted a retrospective study using health data from 229 terminally ill patients (evaluated by our hospital palliative care team (HPCT) hospitalised from January to December 2018. Results: A total of two types of infections were identified: blood flow infection (through blood cultures) and pneumonia (through radiological examinations), while the other cases of infection remained unknown. The most frequently identified microorganism was Staphylococcus spp . The prevalence of infections was higher in patients with non-oncological diseases (n=47, 36.7%; p value 0.009). The potential risk factors identified for infections were the presence of: Parkinson's disease (n=15, 11.7%; p value 0.005), dysphagia (n=49, 38.3%; p value 0.007), bedding (n=15, 11.7%; p value 0.048), pressure ulcers (n=31, 24. 2%); p value 0.018), oxygen therapy (n=60, 46.9%; p value 0.050), urinary catheters (n=95, 74.2%; p value 0.038) and polypathology (2.3 vs 1.7; p value 0.022). Parkinson's disease (OR=5.973; 95% CI=1.292-27.608), dysphagia (OR=2.090; 95% CI=1.080-4.046) and polypathology (OR=1.220; 95% CI=1.015-1.466) were confirmed by a corrected logistic regression analysis. Conclusions: Infections and, consequently, antibiotic therapies, have a high prevalence in hospitalised patients with terminal disease. Potential risk factors for infections in these patients could be polypathology, dysphagia and Parkinson's disease. Patients with these conditions could benefit from prevention programmes.